Immigrant Students and Literacy: Reading, Writing, and Remembering. - Patricia Eugenia Venegas (Networks: An Online Journal for Teacher Research, 2011)
Campano’s book offers a one-of-a-kind invitation for teachers to partake in action research as a fertile foundation for inquiry and for the development of new selves and new literacies. Through critical inquiry and interplay between reality and diversity in a “diaspora community” (p. 73). Campano’s work inspires the construction of flexible and collaborative new knowledge—new knowledge that is embedded in the experiences of teachers and students in and out of school, family histories, and students’ cultural identities. Campano’s fifth-grade immigrant students, all from in an urban California school, engage in a collaborative endeavor that provides a framework for new kinds of learning and literacy development and that reflects culturalhistorical approaches to learning. According to Pacheco & Gutierrez (2009), this approach “focuses on the relation between an individual’s development and the context of development of which the individual student has been a part” (p. 60). Campano’s own life-narrative of his Filipino heritage provides readers with a framework for considering inquiry and development in diverse communities and a rationale for new literacy practices in classrooms.